2002
DOI: 10.1080/1364436022000023211
|View full text |Cite
|
Sign up to set email alerts
|

Empty Wells: How well are we doing at spiritual well-being?

Abstract: This paper presents ten teachers' perceptions of spirituality and considers how these can be categorized. A small research project, recently undertaken, is described. Teachers' stories are contextualised with biographical details, and are presented within a framework of four dimensions of Spirituality (the inner, the social and moral, the environmental and the transcendental) and Spirituality is de ned metaphorically as a hologram with four dimensions. I argue that by viewing spirituality in four broad dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…Fisher (1998) devised a model of spiritual well-being in relation to health, which featured domains of spirituality including personal, communal, environmental and global. Elton-Chalcraft (2002) conducted research with teachers examining their perceptions of spirituality and concluded that the data showed evidence of four dimensions which agreed with other literature in the area. These were defined by the terms: inner, social/moral, environmental and transcendental.…”
Section: Spirituality and Spiritual Literacysupporting
confidence: 77%
See 2 more Smart Citations
“…Fisher (1998) devised a model of spiritual well-being in relation to health, which featured domains of spirituality including personal, communal, environmental and global. Elton-Chalcraft (2002) conducted research with teachers examining their perceptions of spirituality and concluded that the data showed evidence of four dimensions which agreed with other literature in the area. These were defined by the terms: inner, social/moral, environmental and transcendental.…”
Section: Spirituality and Spiritual Literacysupporting
confidence: 77%
“…The examples here show evidence of the suggested dimensions of spirituality relating to the inner and communal aspects and elements of interconnectedness as discussed by Elton-Chalcraft (2002), Fisher (1998) and Ingersoll (1998) respectively.…”
Section: Findings From the Pilotsupporting
confidence: 63%
See 1 more Smart Citation
“…Without true friendships, disabled persons will enjoy the new opportunities created by their equal rights most likely as 'strangers in a strange land'. (Reinders 2008, 187) If spirituality is, among other things, a matter of 'connectedness', which seems to be a reoccurring theme in this journal (Buchanan 2009;Buchanan and Hyde 2008;de Souza 2003;Elton-Chalcraft 2002;, then how do we nurture Galen's Christian spirituality? Can we discern it, measure it or foster it?…”
Section: Introductionmentioning
confidence: 97%
“…The idea that there are four key domains of spiritual well-being, first proposed by the National Coalition on Aging, Washington DC (NICA, 1975), has been supported recently by studies with primary school pupils (in Hay & Nye, 1998 p.120), with secondary school educators (Fisher, 1999a(Fisher, , 2001, university students (Fisher, 2000) and primary school teachers (Fisher, Francis and Johnson, 2002;Elton-Chalcraft, 2002) and Australian 16-20 year-olds (deSouza et al, 2004). The four key domains refer to four different sets of relationship that people have with Self, Others, Nature and/or with God.…”
Section: Introductionmentioning
confidence: 99%